The endoribonuclease activity of mammalian IRE1 autoregulates its mRNA and is required for the unfolded protein response - Tirasophon, Witoon (Cold Spring Harbor Laboratory Press, 2000)
The unfolded protein response (UPR) is a signal transduction pathway that is activated by the accumulation of unfolded proteins in the endoplasmic reticulum (ER). In Saccharomyces cerevisiae the ER transmembrane receptor, Ire1p, transmits the signal to the nucleus culminating in the transcriptional activation of genes encoding an adaptive response. Yeast Ire1p requires both protein kinase and site-specific endoribonuclease (RNase) activities to signal the UPR. In mammalian cells, two homologs, Ire1α and Ire1β, are implicated in signaling the UPR. To elucidate the RNase requirement for mammalian Ire1 function, we have identified five amino acid residues within IRE1α that are essential for RNase activity but not kinase activity. These mutants were used to demonstrate that the RNase activity is required for UPR activation by IRE1α and IRE1β. In addition, the data support that IRE1 RNase is activated by dimerization-induced trans-autophosphorylation and requires a homodimer of catalytically functional RNase domains. Finally, the RNase activity of wild-type IRE1α down-regulates hIre1α mRNA expression by a novel mechanism involving cis-mediated IRE1α-dependent cleavage at three specific sites within the 5′ end of Ire1α mRNA.